Zinc-based Degradable Biomaterials - Limitations and Enhancements - Lovaši, Tomáš; Pinc, Jan; Voňavková, Ilona (Manufacturing Technology Journal, 2019)
Nowadays there is a high trend and effort to find a suitable biodegradable metal, whose mechanical properties would be the same or higher to those of currently used biomaterials. Current biomaterials, such as stainless steels, cobalt-chromium alloys, and titanium alloys have superior mechanical properties, machinability, and durability, but are considered nondegradable, and long-term clinical complications may occur. Their biggest disadvantage is that the patient must have undergone a second removal surgery. Therefore, new biodegradable materials have been developed to eliminate the shortcomings of current biomaterials. Magnesium (Mg), iron (Fe) and zinc (Zn) based alloys have been proposed as biodegradable metals for medical application. Iron-based alloys show good mechanical properties compared to magnesium-based alloys. However, both of them exhibit bad corrosion properties, because the degradation rate of magnesium has proven to be high. On the other hand, the degradation of iron-based alloys is too slow in a physiological environment. The corrosion attack of both materials is not typically uniform. Therefore, zinc is proven to be a promising material for this application.
Keywords: Mechanical properties; corrosion properties; biomaterials; biodegradable metals